Analysis of Standard Clauses in Online Loan Agreements in Indonesia - Dewi Ratih Kumalasari; Yuli Nurmala Sari (Penerbit Goodwood, 2026)
Purpose: This study analyzes standard clauses in online loan agreements in Indonesia, which often cause injustice to consumers. The use of standardized clauses has become increasingly common in digital financial services, but these clauses are often one-sided, favoring the service providers over consumers. This issue can lead to significant legal and ethical concerns. Methodology/approach: This study uses a normative juridical research method with a literature study approach, reviewing relevant regulations, including Law Number 8 Year 1999 on Consumer Protection (UUPK), along with other applicable consumer protection laws in Indonesia. By analyzing the current legal framework and court decisions, the research aims to uncover the practical implications of these clauses. Results/findings: The results indicate that standard clauses such as exoneration clauses, opaque fines, and misuse of personal data often disadvantage consumers by limiting their rights and withholding key information. Conclusions: The use of standard clauses in online loan agreements in Indonesia continues to create problems due to unequal rights and obligations between providers and consumers. Although regulations exist, weak enforcement and low consumer awareness limit effective protection. Limitations: Although the GCPL (Government Consumer Protection Law) has regulated the prohibition of harmful clauses, implementation in the field is still weak due to a lack of supervision, low consumer literacy, and limited access to legal recourse. Contribution: This study highlights the need to strengthen regulations, improve consumer education, and enhance supervision of online loan providers to ensure fair, balanced, and transparent consumer protection.